A Comparative Pharmaco-Analytical Study of Vyoshadi Gutika and its Modified Dosage Form w.s.r. to Lozenges. - Sharma, Vikash; Chaudhari, Mukesh (International Research Journal of Ayurveda & Yoga, 2024)
Ayurveda is the science of life and one of the world’s oldest holistic healing system. Its aim is to prevent disease formation along with cure of diseased ones. For both of the purpose it advocates use of metal, minerals and herbal compounds in treatment of various Diseases. Ancient dosage forms are good but it needs some modification regarding its palatability, shelf life and marketing feasibility. The new dosage forms of herbal and herbo-mineral formulations in Ayurveda are – Tablets, Capsules, Lozenges, Ointment, gel, creams, Balms, Lotions, Granules etc. All these formulations have their Boons and Banes. Vyoshadi Gutika is used for Pratishyay. It is a chewable tablet, but its contents are Ushna and tikshna due to which it is difficult to take. Modification of Vyoshadi Gutika into Lozenges will make it easier to take and probably more effective due to keeping it for long time in mouth. Lozenges are the solid, unit dosage form that contains one or more medicaments, usually in a flavored, sweetened base, that are intended to dissolve or disintegrate slowly in the mouth. Development of lozenges dates back to 20th century and is still in commercial production. New dosage form has several benefits like easy to use, more effective, better presentation etc. On the other hand, they also have few demerits like expensive, change in formulas, added sugars etc.